PROSEDUR PERTANGGUNGJAWABAN KEGIATAN OPERASI PASAR OLEH PT. JATIM GRHA UTAMA - Putra, Maulana Yogi Aditya Dwi; Anisykurilillah, Rosyidatuzzahro (Peneliti.net, 2023)
This study aims to analyze the process of reporting accountability for market operations by PT. JGU. The research method used is qualitative research using case studies as an approach. Direct observation and direct interviews of the accountability reporting process. Data is collected through documentation related to activity accountability archives at PT. JGU. Data analysis was performed using content analysis techniques. The results of the study indicate that there are many obstacles to the process of reporting activities, the application of digitalization in the accountability reporting process of PT. JGU is possible to provide a number of benefits. The use of digital technology allows easier and faster data storage and search. Historical data can be easily accessed and used for further analysis, evaluation or reporting purposes. In addition, digitization also allows easy collaboration between teams or departments in preparing and monitoring accountability reports more efficiently.